The Role of Career Satisfaction in Mediating the Relationship Between Career Planning to Turnover Intention (Case Study of Employee on PT. Bank Rakyat Indonesia (Persero) Tbk. Semarapura Branch) - Indrayani, Ketut Sri Wahyuni; Riana, I Gede (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
This study aims to analyse the role of career satisfaction, career planning, and employee turnover intention at PT Bank Rakyat Indonesia (Persero) Tbk. Semarapura Branch. This study used a sample of 36 people determined based on saturated sampling technique. The method used in this research is observation and survey method with questionnaire and interview techniques with inferential statistical analysis tool path analysis. The results showed that career planning has a negative and significant effect on turnover intention. Career planning has a positive and significant effect on career satisfaction. Career satisfaction has a negative and significant effect on turnover intention. Career satisfaction mediates the relationship between career planning and turnover intention. The implication of this research is to prove the traditional turnover theory and its relation to the research variables. This research also offers the benefits of career satisfaction, managing career planning on turnover intention.